Pandangan Islam Tentang Aborsi - Nasution, Khoiruddin (Musawa Jurnal Studi Gender dan Islam, 2003)
There is controversy over whether or not abortion should beÂ· allowed. However Islamic thinkers agree that abortion may be carried out in cases where the pregnancy threatens the life of the mother. In the writer's opinion, the prohibition on abortion has been made for certain reasons, and conversely there are certain reasons or conditions under which abortion can be tolerated. These certain conditions may include pregnancy as a result of rape, pregnancy as Â·a result of incest, disturbances in the physical health of the mother even though they are not life threatening, mental health problems, disability of the foetus and so on. These factors will have a strong impact on the life of the child as well as that of the mother, and as such, these indications can be reasons to allow abortion.